The Nutrition Knowledge of Primary Care Physicians in the State of Qatar - Daradkeh, Ghazi A.F.; Al Bader, Khalid; Singh, Rajvir (Pakistan Journal of Nutrition, 2012)
To determine the nutritional knowledge of primary care physicians. A validated questionnaire with multiple-choice questions were distributed to 136 physicians, working in various health care centers in the state of Qatar between Jan 2009 to Jun 2009. Completed questionnaire were received from 136 of 225 physicians (60.4% the mean score for correctly answered questions was (64%). Approximately 19% of the physicians describe their knowledge of nutrition as very good, 60% as moderate and 21% as poor. The results indicate that physicians are generally aware of nutritional information related to common prevalent topics related to nutrient believed to help prevent thrombosis Major type of fat in olive oil, the preventive action of fruits and vegetables against cancer, toxic vitamins if consumed excessively and the nutrients associated with the prevention of neural tube defects. In contrast physicians showed poor knowledge regarding other important topics in nutrition, such as the role of soluble fibers in lowering blood cholesterol, the lowest glycemic index foods, the main fatty acid formed in the egg, substance raises the blood HDL-cholesterol level and the association between excess protein intake and calcium less. These results showed that physicians need more education in nutrition. Nutrition should be an essential part in the continuing medical education.